STRATEGI PEMBELAJARAN MASTER PADA MATA PELAJARAN PENDIDIKAN AGAMA HINDU DI SD NEGERI DESA TINGGARSARI KECAMATAN BUSUNGBIU KABUPATEN BULELENG - Komang Agus Triadi Kiswara (UNHI PRESS, 2022)
The main task of Hindu religious teachers is to transform knowledge to students in order to have srada (faith) and devotion (taqwa) to God Almighty. In the learning process that is carried out, the teacher often experiences several obstacles that come from the teacher's internal and external nature, for this reason, a learning strategy is needed to be able to overcome these obstacles. The learning strategy used by Hindu religious education teachers at SD Negeri Tinggarsari is MASTER, namely, an independent learning strategy developed by Rose and Nicholl. MASTER is an acronym for Mind, namely the use of learning styles, Acquire, which is to get core ideas, Search out, namely learning with a supervisor, Triger builds motivation, Exhibit is an assessment, Reflect means a combination of what is known then and now. The purpose of this study was to determine the rationale for the use of MASTER learning strategies in Hindu religious education learning at SD Negeri in Tinggarsari, the methods of cultivation, constraints and impacts of learning with MASTER learning strategies. The theory used to solve this problem is Cognitive theory, structural functional theory. , and behavioristic theory. This research is in the form of a qualitative design where the data were collected using observation techniques, interview techniques and document study techniques. After the data has been collected, it is analyzed using qualitative methods through three steps, namely data reduction, data verification, drawing conclusions and data presentation. The results of the research produced in this study, the reason teachers at SD Negeri in Tinggarsari use the MASTER strategy in Hindu religious education learning is the achievement of the goal of Hindu religious education, namely forming students who have srada and Bhakti, forming student characters in accordance with the teachings of Hinduism. , instilling values that exist in society, active, creative, effective and fun learning. The application of the MASTER learning strategy through two stages, namely planning and implementing learning. The resulting impact is the creation of conducive learning for students. ABSTRAK Tugas utama dari guru Agama Hindu adalah mentransformasi pengetahuan kepada peserta didik agar dapat memiliki srada (keimanan) dan bhakti (taqwa) kepada Tuhan Yang Maha Esa. Dalam proses pembelajaran yang dilakukan, guru sering mengalami beberapa kendala-kendala yang sifatnya dating dari internal guru maupun eksternalnya, untuk itulah diperlukan sebuah strategi pembelajaran untuk dapat mengatasi kendala tersebut. Strategi pembelajaran yang di pakai oleh guru pendidikan Agama Hindu di SD Negeri Tinggarsari adalah MASTER yaitu, strategi pembelajaran mandiri yang dikembangkan oleh Rose dan Nicholl. MASTER merupakan akronim Mind yaitu penggunaan gaya belajar, Acquire yaitu memperoleh gagasan inti, Search out yaitu belajar bersama pembimbing, Triger membangun motivasi, Exhibit adalah penilaian, Reflect artinya adalah perpaduan apa yang diketahui dahulu dan sekarang. Tujuan penelitian ini adalah Untuk mengetahui dasar pikiran digunakannya strategi pembelajaran MASTER dalam pembelajaran pendidikan Agama Hindu di SD Negeri di Tinggarsari, cara penarapan, kendala-kendala serta dampak dari pembelajaran dengan strategi pembelajaran MASTERTeori yang digunakan untuk memecahkan masalah ini adalah teori Kognitif, teori fungsional struktural, dan teori behavioristik. Penelitian ini berbentuk rancangan kualitatif dimana data dikumpulkan denga n menggunakan teknik observasi, teknik wawancara dan teknik studi dokumen. Setelah data terkumpul kemudian dianalisa dengan metode kualitatif yang melalui tiga langkah yaitu reduksi data, verifikasi data, penarikan kesimpulan dan penyajian data. Hasil penelitian yang dihasilkan dalam penelitian ini,Alasan guru- guru di SD Negeri di Tinggarsari memakai strategi MASTER dalam pembelajaran pendidikan Agama Hindu adalah, tercapainya tujuan pendidikan Agama Hindu yaitu membentuk siswa yang memiliki srada dan Bhakti, membentuk karakter siswa yang sesuai dengan ajaran agama Hindu, menanamkan nilai- nilai yang ada di masyarakat, pembelajaran yang aktif, kreatif, efektif dan menyenangkan. Penerapan strategi pembelajaran MASTER melalui dua tahap yaitu perencanaan dan penerapan pembelajaran.Dampak yang dihasilkan adalah terciptanya pembelajaran yang kondusif bagi siswa.